2016
DOI: 10.3847/0004-637x/832/2/157
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Pseudobulge Galaxy Launching Powerful Relativistic Jets

Abstract: Supermassive black holes launching plasma jets at close to the speed of light, producing gamma-rays, have ubiquitously been found to be hosted by massive elliptical galaxies. Since elliptical galaxies are generally believed to be built through galaxy mergers, active galactic nuclei (AGN) launching relativistic jets are associated with the latest stages of galaxy evolution. We have discovered a pseudobulge morphology in the host galaxy of the gammaray AGN PKS 2004-447. This is the first gamma-ray emitter radio-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 49 publications
3
60
0
Order By: Relevance
“…6). Imaging of PKS2004-447 ( [82]) revealed a (pseudo)bulge plus disc and bar, and no evidence for a recent merger. [33], using the GTC 10m telescope, reported evidence for an elliptical host of FBQSJ1644+2619, while [108] prefer a barred lenticular (SB0) host galaxy model of FBQSJ1644+2619, with a pseudo-bulge and a ring, perhaps the aftermath of a minor merger.…”
Section: Inferences From Optical Imaging and Spectroscopy 71 Host Gamentioning
confidence: 97%
“…6). Imaging of PKS2004-447 ( [82]) revealed a (pseudo)bulge plus disc and bar, and no evidence for a recent merger. [33], using the GTC 10m telescope, reported evidence for an elliptical host of FBQSJ1644+2619, while [108] prefer a barred lenticular (SB0) host galaxy model of FBQSJ1644+2619, with a pseudo-bulge and a ring, perhaps the aftermath of a minor merger.…”
Section: Inferences From Optical Imaging and Spectroscopy 71 Host Gamentioning
confidence: 97%
“…Olguín-Iglesias et al (2017) found FBQS J1644+2619 to reside in a barred lenticular galaxy showing signs of a recent minor merger, but D' Ammando et al (2017) argue that the host is an elliptical galaxy. PKS 2004-447 seems to reside in a barred disklike galaxy (Kotilainen et al 2016), and PKS 1502+036 in an elliptical galaxy (D'Ammando et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However Red spirals and Speca-like radio galaxies may still contain signs of their earliest behaviour like "vestigial organs". Indeed, existance of psudo-bulge in J2345-0449 and newly discovered, gamma-ray emitting, radio loud, narrow-line Seyfert 1 galaxy PKS 2004-447 firmly support secular evolutionary processes (not merger-driven) for these rare systems (Oshlack, Webster & Whiting (2001), Kormendy & Kennicutt (2004), Abdo et al 2009, Kotilainen et al, 2016. Thus, Speca-like galaxies may indeed be the "living fossil" or opportunity to learn about first massive spirals formed with massive black holes in their centres in the early Universe.…”
Section: Fig 8: Radio-optical Image Of Speca Based On Hota Et Al (mentioning
confidence: 89%